Being agile : your roadmap to successful adoption of agile - Moreira, Mario E. (Apress, 2013)
Being Agile is your roadmap to successfully transforming your organization to an Agile culture. Veteran agile coach Mario Moreira teaches new adopters how to implement a robust Agile framework to derive from it the maximum business benefit in terms of customer value, revenue, and employee engagement. Agile is a ubiquitous watchword in the corporate world, but only a minority of companies understand and practice what they pay lip service to. Too many content themselves with half-baked approximations such as Fragile (fragile Agile), ScrumBut (Scrum but not the practices), and Scrum Fall (mini-waterfalls in the sprints). Moreira shows maturing early adopters how to bridge the chasm between going through the motions of doing Agile and genuinelybeing Agile. After a high-level synopsis of Agiles values and principles, methodologies (including Scrum, Kanban, DSDM, Leam, VFQ, and XP), and roles, Moreira plunges into the nitty-gritty of how to apply the ready, implement, coach, and hone (RICH) deployment model to all phases of a project in such a way as to embody and inculcate agile values and principles at the team level and promote agile transformation across your organization's culture.